Demon slayer = Kimetsu no yaiba. Volume 22, The wheel of fate - Gotoge, Koyoharu, 1988-; Stan!, 1964- (Shonen Jump manga., 2021)
"After centuries of preparation and training, the Demon Slayer Corps has come face-to-face with their nemesis, Muzan Kibutsuji. It is a desperate battle and several Demon Slayers have already been killed. Tanjiro himself has engaged Muzan, and, despite giving it everything he has, is taken out of the fight! Although severely injured and near death, he sees a vision of his ancestor that may hold the key to finally destroying Muzan! Can Tanjiro recover enough strength to fight Muzan to the finish?"--